Dynamic analysis of Caribbean food import demand - David Forgenie; Sharon D. Hutchinson; Andrew Muhammad (Journal of Agriculture and Food Research, 2024)
Short- and long-run price and income elasticities are generally unavailable at the regional level for major imported food groups for the Caribbean. These elasticity measures are needed to enhance policymaking. This paper therefore seeks to determine the income, own-price and cross-price elasticities of eight major imported food groups. This will show the relationships between income and price changes on the import quantities for the major food groups. This was done using an error-corrected linear approximate almost ideal demand system (EC-LA-AIDS) for the period 1961–2021, using annual data. The study found that the theoretical restrictions of homogeneity and symmetry did not hold in the static LA-AIDS model but did in the EC-LA-AIDS model. The speed of adjustment parameter in the EC-LA-AIDS model revealed that imported beverages had the slowest adjustment to long-run equilibrium while all other imported food categories had a moderate adjustment speed. The study also derived short- and long-run income and price elasticities of import demand for the eight imported food categories. In both time horizons, income elasticities revealed that all imported food categories were normal goods. In both time horizons, imported meat and seafood, and sugar and honey were the most responsive to changes in income, while spices and tea was the least responsive. Own-price elasticities revealed that all imported food categories were import price inelastic except for meat and seafood which was found to be import price elastic in both time horizons. Additionally, cross-price elasticities unveiled various substitution and complementary relationships between pairs of imported foods. The study not only contributed empirical insights into the import demand dynamics of the Caribbean, but also emphasized significant policy implications arising from the research findings.